Investigating Local Community Perception towards English Language Volunteer Tourism: Case Study in A Balinese Village - Suprastayasa, I Gusti Ngurah Agung; Adi, Ida Ayu Sri Puspa; Ariasri, Nyoman Reni (Jurnal Penelitian Pariwisata, 2025)
Volunteer tourism has become a trend where individuals engage in voluntary work while traveling. Volunteer teaching English as a foreign language stands out as one of the activities. This study aimed at investigating the local community perception towards a volunteer teaching English program in a village in Bali. This study employed a qualitative research approach, utilizing semi-structured interviews as the primary data collection method. The finding showed that the local community, whether they participated as students or not, highly appreciated and had a positive attitude toward the volunteer tourism program. They viewed only the positive sides of the activities since this was the first such volunteer program conducted in their village. Further studies need to be conducted for investigating the local community perception of receiving longer periods or more frequent English volunteer programs. Keywords: volunteer tourism, educational tourism, English as a foreign language